The Quality of Assessment for Learning score for evaluating written feedback in anesthesiology postgraduate medical education: a generalizability and decision study (Canadian Medical Education Journal, 2023)
Background: Competency based residency programs depend on high quality feedback from the assessment of entrustable professional activities (EPA). The Quality of Assessment for Learning (QuAL) score is a tool developed to rate the quality of narrative comments in workplace-based assessments; it has validity evidence for scoring the quality of narrative feedback provided to emergency medicine residents, but it is unknown whether the QuAL score is reliable in the assessment of narrative feedback in other postgraduate programs.Methods: Fifty sets of EPA narratives from a single academic year at our competency based medical education post-graduate anesthesia program were selected by stratified sampling within defined parameters [e.g. resident gender and stage of training, assessor gender, Competency By Design training level, and word count (≥17 or